2007
DOI: 10.1007/s10765-007-0283-y
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of the Realization of the ITS-90 at the Freezing Points of Al and Ag among European NMIs

Abstract: The EUROMET.T-K4 comparison is the regional extension of CCT-K4, an intercomparison of the realizations of the freezing points of Al (660.323 • C) and .78 • C). The intercomparison was organized in four loops. Long-stem standard platinum resistance thermometers (SPRTs) were used as traveling standards: 25 thermometers to be used only at the Al freezing point and two high-temperature standard platinum resistance thermometers (HTSPRTs) to be used only at the Ag freezing point in each loop. Parallel to the measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The difference between measurements made at VSL and MIRS/UL-FE/LMK was −1.7 mK, with an uncertainty of 4.2 mK. Furthermore, the difference between laboratories established during the EURA-MET 820 (T.K4) [3] intercomparison was −2.73 mK with an uncertainty of 5.70 mK, as shown in Fig. 3.…”
Section: Results and Linkage To Euramet 820 (Tk4)mentioning
confidence: 85%
See 2 more Smart Citations
“…The difference between measurements made at VSL and MIRS/UL-FE/LMK was −1.7 mK, with an uncertainty of 4.2 mK. Furthermore, the difference between laboratories established during the EURA-MET 820 (T.K4) [3] intercomparison was −2.73 mK with an uncertainty of 5.70 mK, as shown in Fig. 3.…”
Section: Results and Linkage To Euramet 820 (Tk4)mentioning
confidence: 85%
“…On the graph, the actual measurements at the freezing point of aluminum at each phase of the bilateral comparison can be seen together with their uncertainties. The detailed budget of uncertainties is presented in Table 2 [3]. During the bilateral comparison, the change of resistance value of the used SPRT at the triple point of water can be seen in Fig.…”
Section: Results and Linkage To Euramet 820 (Tk4)mentioning
confidence: 99%
See 1 more Smart Citation
“…The current uncertainty budget for the calibration of SPRTs in the range from the mercury triple point to the aluminum freezing point is presented in Table 1. As can be seen from the uncertainty budget for the calibration of SPRTs at the aluminum freezing point, presented in Table 2 for Euromet Project 820 [4], the limiting factor is the uncertainty due to the DC/AC current, which is affected by the available power source. The laboratory is located where an ever-growing number of nonlinear electrical loads (such as computers, air conditioning systems, etc.)…”
Section: Measurement Techniques and Uncertaintiesmentioning
confidence: 99%
“…Over the past 20 years, the reliability and performance of HTSPRTs have been troubled by instability and short circuits in the sensor coils. During the European Association of National Metrology Institutes (EUROMET) regional key comparison, EUROMET.T-K4 found that the selected HTSPRTs were M. Zhao (B) · D. Chen · M. Newman · R. Ding Fluke Corporation, Hart Scientific Division, American Fork, UT 84003, USA e-mail: mingjian.zhao@hartscientific.com less stable than desired, and one of the Bureau International des Poids et Mesures (BIPM) HTSPRTs failed due to a short circuit in the sensor [1]. Similar problems were reported in other laboratories such as the National Metrology Institute of Japan (NMIJ).…”
Section: Introductionmentioning
confidence: 99%